EXPERIENCE OF ORNITHINE ASPARTATE (HEPA-MERZ) AND PROBIOTICS BIOFLORUM FORTE IN THE TREATMENT OF NON-SEVERE FORMS OF ALCOHOLIC AND NON-ALCOHOLIC FATTY LIVER DISEASE - L. Yu. Ilchenko (Arhivʺ Vnutrennej Mediciny, 2016)
Aim: to evaluate the efficacy and tolerability of ornithine aspartate, probiotic Bioflorum Forte and their combination with steatosis and steatohepatitis in patients  with alcohol and non-alcoholic  fatty  liver disease. Materials and methods.  An open, randomized,  comparative  clinical study, which included 30 outpatients and inpatients with a diagnosis of steatosis, steatohepatitis. We analyzed the clinical symptoms, functional state of the liver. With the help of questionnaires  (Grids LeGo and post intoxication alcohol syndrome) have established the presence of chronic alcohol intoxication. Test transmissions of numbers used to characterize the cognitive function, as well as detection  of minimal hepatic encephalopathy. Quality of life was assessed by questionnaire for patients with chronic liver disease — CLDQ (The chronic liver disease questionnaire). The duration of treatment was4 weeks. Results: all three treatment regimens have demonstrated therapeutic  efficacy: clinical improvement, recovery of liver function and results in cognitive function. When combined therapy also produced a significant improvement  in patients’ quality of life. It is shown that  the safety and tolerability of the means employed, adverse events were not reported. Conclusion: the results obtained allow us to recommend the use of ornithine aspartate (Hepa-Merz), both as monotherapy and as part of complex therapy of steatosis,  steatohepatitis with probiotic Bioflorum Forte in patients with alcoholic and non-alcoholic fatty liver disease.